Systemic corticosteroids for acute sinusitis. - Venekamp, R; Thompson, M; Hayward, G; Heneghan, C; Mar, D; Perera, R; Glasziou, P; Rovers, M (2011)
BACKGROUND: Acute sinusitis is a common reason for patients to seek primary care consultations. The related impairment of daily functioning and quality of life is attributable to symptoms such as facial pain and nasal congestion. OBJECTIVES: To assess the effectiveness of systemic corticosteroids in relieving symptoms of acute sinusitis. SEARCH METHODS: We searched the Cochrane Central Register of Controlled Trials (CENTRAL) Issue 2, 2011, which includes the Acute Respiratory Infections (ARI) Group's Specialised Register, the Database of Reviews of Effects (DARE) and the NHS Health Economics Database, MEDLINE (1966 to June week 2, 2011) and EMBASE (January 2009 to June 2011). SELECTION CRITERIA: Randomised controlled trials (RCTs) comparing systemic corticosteroids to placebo or standard clinical care for patients with acute sinusitis. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed methodological quality of the trials and extracted data. MAIN RESULTS: Four RCTs with a total of 1008 adult participants met our inclusion criteria. We judged studies to be of moderate methodological quality. Acute sinusitis was defined clinically in all trials. However, the three trials performed in ear, nose and throat (ENT) outpatient clinics also used radiological assessment as part of their inclusion criteria. All participants received oral antibiotics and were assigned to either oral corticosteroids (prednisone 24 mg to 80 mg daily or betamethasone 1 mg daily) or the control treatment (placebo in three trials and non-steroidal anti-inflammatory drugs (NSAIDs) in one trial). In all trials, participants treated with oral corticosteroids were more likely to have short-term resolution or improvement of symptoms than those receiving the control treatment: at Days 3 to 7, risk ratio (RR) 1.4, 95% CI 1.1 to 1.8; risk difference (RD) 20% (6% to 34%) and at Days 4 to 10 or 12, RR 1.3, 95% CI (1.0 to 1.7), RD 18% (3% to 33%). An analysis of the three trials with placebo as a control treatment showed similar results but with a lesser effect size: Days 3 to 6: RR 1.2, 95% CI (1.1 to 1.4), RD 12% (5% to 19%) and Days 4 to 10 or 12: RR 1.1, 95% CI (1.0 to 1.2), RD 10% (3% to 16%). Scenario analysis showed that outcomes missing from the trial reports might have introduced attrition bias (a worst-case scenario showed no statistically significant beneficial effect of oral corticosteroids). We did not identify any data on the long-term effects of oral corticosteroids on this condition, such as effects on relapse or recurrence rates. Reported side effects of oral corticosteroids were limited and mild. AUTHORS' CONCLUSIONS: Current evidence suggests that oral corticosteroids as an adjunctive therapy to oral antibiotics are effective for short-term relief of symptoms in acute sinusitis. However, data are limited and there is a significant risk of bias. High quality trials assessing the efficacy of systemic corticosteroids both as an adjuvant and a monotherapy in primary care patients with acute sinusitis should be initiated.